RHIZOSPHERE MICROBIOME, SOIL ENZYMES AND GROUNDNUT YIELD AS INFLUENCED BY ADDITION OF BIOCHAR AND FERTILIZERS IN IRRIGATED ALFISOL OF NORTH COASTAL ANDHRA PRADESH - B. GOWTHAMI and P. GURUMURTHY*, (The Journal of Research ANGRAU, 2024)
The field experiment was conducted in irrigated Alfisols of North coastal Andhra Pradesh tostudy the effect of biochar and chemical fertilizers on rhizosphere microbiome, soil enzymes andyield performance of groundnut crop (variety K-6) during rabi, 2018-19. Biochar application tosoil significantly increased soil bacterial, fungal and actinomycetes population. At pod developmentstage, the highest number of bacterial count (39.0 x106 CFU g-1 soil) was observed in T5 (100%RDF + biochar @ 6 t ha-1) which was on par with all the biochar applied treatments (T3, T4, T6, T7,T8). The Biochar applied @ 6 t ha-1 (T5 & T8) significantly increased the bacterial population ascompared to non-biochar applied treatments (T1 & T2). Fungal and actinomycetes populationfollowed the similar trend of bacterial count. Soil urease activity was significantly superior inbiochar applied treatments (T3, T4, T5, T6, T7, T8) compared to non biochar applied treatments (T1and T2). With increased rates of biochar application the urease activity markedly increased insoil. Similar trend was noticed with respect to dehydrogenase, acid phosphatase and alkalinephosphatase enzymes in soil in response to addition of biochar. At pod development stage, thehighest leaf area index (3.16) was recorded with 100% RDF + biochar @ 6 t ha-1(T5) which wassignificantly higher than T1 (control), T2 (100% RDF) and T6 (75% RDF + biochar @ 2 t ha-1). Thehighest drymatter accumulation of 2951 kg ha-1 at peg penetration and 6428 kg ha-1 at poddevelopment was observed in T5 (100% RDF + biochar @ 6 t ha-1) which was on par with T3(100% RDF + biochar @ 2 t ha-1), T4 (100% RDF + biochar @ 4 t ha-1), T8 (75% RDF + biochar @6 t ha-1) treatments. Groundnut pod yield was highest (4019.58 kg ha-1) in treatment received100% RDF + biochar @ 6 t ha-1, which was on par with T4 (100% RDF + biochar @ 6 t ha-1) and T8(75% RDF + biochar @ 6 t ha-1).